Molecular characterization of lepotospira isolates from rodents, soil, and water in Sarawak using ERIC-PCR - Intan Syahirah, Amran (Universiti Malaysia Sarawak (UNIMAS), 2016)
Leptospirosis is endemic to tropical regions of the world and is re-emerging as a new danger to public health in Southeast Asia, including Malaysia. The aim of this study was to evaluate molecular typing of Leptospira spp. by using Enterobacterial Repetitive Intergenic Consensus (ERIC-PCR) as a tool. A total of 70 samples were obtained from the culture collection in Microbiology Laboratory FRST, UNIMAS. The samples was cultured into semi solid EMJH media added with 5-fluorouracil. The cultures were incubated at room temperature (28-30°C) for 30 days before ERIC-PCR was conducted. This procedure was used a specific primer which is ERIC 1 (ATGTAAGCTCCTGGGGATTCAC) and ERIC2 (AAGTAAGTGACTGGGGTGAGCG) that targeting ERIC sequence. The ERIC elements were used as a genetic marker to characterize isolates within bacterial species. Though, by using PyElph 1.4 software to construct the phylogenetic tree to know the similarity coefficient levels and calculating by using DI (Diversity Indices'). From that, there are no proper arrangement of bacteria in the group regardless of samples type whether it mix together to 7 groups and also of Leptospira in different location and sources. In conclusion, genetic relatedness between Leptospira spp are studied and allow their characterization among the type of samples isolates.